Small states and the big European migration crisis - Luša, Đana (Teorija in praksa, 2019)
The article analyses EU small states' border policies in response to the European migration crisis from the summer of 2015 to March 2016, when the Western Balkan route was closed. Migration system theory and the theory of policy convergence are applied to study migration from a small-state perspective. Changes within the EU system and their influence on such states' border policies, the difference between destination and transit small states, along with small states' foreign policy strategies are addressed in particular. The dilemma for small states is between harmonising with the established EU policies or projecting autonomy by making certain unilateral moves while dealing with migrant flows at the borders. This article contributes to the scarce literature on migration from a small-state perspective, especially by analysing the experiences and dilemmas they share and the challenges arising from migrations. Croatia, Slovenia, Austria, Denmark and Sweden are used as case studies.
Keywords: EU; Evropa; male države; migracije; migrantska kriza; sistemska teorija migracij; teorija zbliževanja politik